Composition inversion to form calcium carbonate mixtures. Issue 26 (11th May 2017) - Peh, Eddie; Liedel, Clemens; Taubert, Andreas; Tauer, Klaus
Abstract : A solid mixture of reactants undergoes composition inversion to form calcium carbonate. Abstract : Composition inversion takes place in equimolar solid mixtures of sodium or ammonium carbonate and calcium chloride with respect to the combination of anions and cations leading to the corresponding chloride and calcite in complete conversion. The transformation takes place spontaneously under a variety of different situations, even in a powdery mixture resting under ambient conditions. Powder X-ray diffraction data and scanning electron microscopy micrographs are presented to describe the course of the reaction and to characterize the reaction products. The incomplete reaction in the interspace between two compressed tablets of pure starting materials leads to an electric potential due to the presence of uncompensated charges.